METHODOLOGY FOR ORGANIZING INDEPENDENT EDUCATION IN THE TRAINING OF THE MODULE " ANALYZERS - Teshajonova Mahliyo Marufjon qizi (Scholar Express Journal, 2022)
In the National Personnel Training Program, along with in-depth theoretical and practical knowledge, one of the main tasks is to train specialists who can independently operate in their chosen field, independently improve their knowledge and qualifications, correctly identify problem situations with a creative approach to the issue and quickly adapt to the conditions. It is knownthat in the current conditions, when the range of information and knowledge is rapidly expanding, it is difficult to convey all information to students only during class time.
Keywords: analyzers, leader, student, mustail education, methods, stage of study , level of difficulty, human anatomy and physiology, layout ,model.